Quantum Spin Hall Materials (Adv. Quantum Technol. 10/2019). Issue 10 (15th October 2019) - Cao, Chuanwu; Chen, Jian‐Hao
Abstract : The cover image shows a semi‐classical model of quantum spin Hall (QSH) effect, where the bulk of a two‐dimensional system is insulating and counter‐propagating spin‐polarized electrons move along its edges without dissipation. The edge states are protected by time‐reversal symmetry and insensitive to disorders. The unique edges of QSH materials provide a route to generate and detect Majorana fermions, which is a possible solution on quantum computing. In article number 1900026, Chuanwu Cao and Jian‐Hao Chen review the development of the understanding and construction of the QSH states with an emphasis on the materials perspective.